Studying the Factors Affecting the Settling Velocity of Solid Particles in Non-Newtonian Fluids - Mohammed, Muhanned A.R.; Halagy, Dina Adil Elia (Nahrain University College of Engineering Journal, 2017)
The aim of this research is to study the factors affecting the settling velocity (V S ) in Non-Newtonian fluids which are the rheological properties, concentrations of non-Newtonian fluids, particle shape and size.An experimental apparatus was designed and built, which consists of Perspex pipe of length of 160 cm. and inside diameter of 7.8 cm. to calculate the settling velocity, also electronic circuit was designed to calculate the falling time of particles through fluid.Two types of solid particles were used; glass spheres and crushed rocks as irregularly shaped particles with different diameters and compared with each other. The concept of equivalent spherical diameter (D S ) was used to calculate the diameters of irregularly shaped particles.The settling velocity was calculated for Non-Newtonian fluids which represented by Power- Law fluid. Two types of polymers were used, Carboxy Methyl Cellulose with concentrations of (3.71, 5, 15 and 17.5) g/l and polyacrylamide with concentrations of (2, 4 and 6) g/l.The results showed that the settling velocity decreased when fluid becomes far from Newtonian behavior (flow index n decreased) and also when concentrations of polymer solutions increased, also, the settling velocity increased with particle diameter or volume. Three sets of equations were concluded; the first relates settling velocity with flow index (n), the second relates settling velocity with concentrations, and the third relates settling velocity with particle diameter.